The Pebble Mine Dialogue: A case study in public engagement and the social license to operate. (March 2016) - Holley, Elizabeth A.; Mitcham, Carl
Abstract: The Pebble gold–copper–molybdenum deposit is a controversial mining project in the headwaters of the Bristol Bay salmon fishery, Alaska. As a member of the Pebble Limited Partnership, the mining company Anglo American sponsored a public engagement exercise to help stakeholders decide whether and how the deposit should be mined. The independent Keystone Policy Center facilitated the dialogue, which positioned science as a means of enhancing public rationality. Stakeholders for and against the mine reviewed the mining partnership's environmental baseline study data but did not reach consensus on whether risks posed to the salmon fishery were too great. Anglo American left the partnership, and the Pebble Dialogue was not completed. The final planned phase of the dialogue involved collaborative community–company mine planning in what would have been a high-impact mechanism of CSR, but negotiations of the risks and benefits to stakeholders did not take place. The mining project has not achieved social license, although the Pebble Dialogue offers some components that should be considered in future public engagement exercises. Highlights: Pebble, Alaska is a controversial mining project upstream of a salmon fishery. The public engagement exercise addressed whether and how the deposit should be mined. The dialogue positioned science as a means of enhancing public rationality. Stakeholder opinion remains divided, and social license was not obtained. Negotiation of risks and benefits is critical in early stages of public engagement.